Hollow CoS/C Structures for High-Performance Li, Na, K Ion Batteries - Liu, Yan; Li, Xiangkun; Zhang, Fengling; Zhang, Leqing; Zhang, Tao; Li, Changshuan; Jin, Zhicheng; Wu, Yueying; Du, Zhongyu; Jiao, Huiwen; Jiang, Ying; Yan, Yuliang; et al. (Frontiers in Chemistry, 2022)
Alkali ion (Li, Na, and K) batteries as a new generation of energy storage devices are widely applied in portable electronic devices and large-scale energy storage equipment. The recent focus has been devoted to develop universal anodes for these alkali ion batteries with superior performance. Transition metal sulfides can accommodate alkaline ions with large radius to travel freely between layers due to its large interlayer spacing. Moreover, the composite with carbon material can further improve electrical conductivity of transition metal sulfides and reduce the electron transfer resistance, which is beneficial for the transport of alkali ions. Herein, we designed zeolitic imidazolate framework (ZIF)–derived hollow structures CoS/C for excellent alkali ion (Li, Na, and K) battery anodes. The porous carbon framework can improve the conductivity and effectively buffer the stress-induced structural damage. The ZIF-derived CoS/C anodes maintain a reversible capacity of 648.9, and 373.2, 224.8 mAh g−1 for Li, Na, and K ion batteries after 100 cycles, respectively. Its outstanding electrochemical performance is considered as a universal anode material for Li, Na, and K ion batteries.